Из истории лидийско- египетских взаимоотношений в VII в. до н.э. - Соловьева, С. С.
Solov'eva = Solovjova, S. S., From the History of the Relations Between Lydia and Egypt in the VIIth Century B.C.; engl. Résumé S. 254: Assurbanipal-Annalen auf 655/4 zu beziehen.